How serious is a devolved data deficit? A Welsh perspective. (December 2018) - Crawley, Andrew; Munday, Max; Roberts, Annette
Over the last decade the UK has seen greater fiscal devolution with both Wales and Scotland gaining additional powers. However, to date, such devolution has not been sufficiently accompanied by an increase in the production of more local economic data to assist policymaking choices. The paper considers this issue by first exploring, in general, the availability of local economic data with a focus on Input–Output tables and trade statistics. The case of Wales is then used to explore the problems associated with the lack of local economic data. The paper suggests that not providing the means to assess how fiscal policy might impact economic performance could present a particularly serious challenge for devolved governments. The conclusions discuss how a devolved data deficit might be overcome in a cost-effective manner.